Acceleration of stunting reduction: Advancing social and environmental well-being through policy, education, and environmental management - Firdaus, Samuel Evan; Maulana, Precious Douglas (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Stunting is a serious public health problem in Indonesia, especially in East Nusa Tenggara/Nusa Tenggara Timur (NTT) Province, which has a high prevalence. Based on the 2021 Indonesian Nutritional Status Survey (SSGI), there are 15 districts in NTT with stunting rates of more than 30%, even in South Central Timor and North Central Timor Regencies, the prevalence reaches more than 46%. The main factors contributing to stunting include malnutrition, poor sanitation, and consanguineous marriage practices. Methods: This study uses a literature review approach by applying the Social Ecological Model (SEM) to analyze risk factors and intervention strategies. The data used include empirical studies and policies related to stunting in NTT. Findings: The analysis shows that poor sanitation, such as access to clean drinking water which only reaches 86.79% and access to proper sanitation of 73.7%, is correlated with high stunting rates. Data also show that low milk consumption, with an average consumption of only 30 kilocalories per capita per day in Southeast Asia, contributes to the high prevalence of stunting of 31%. In addition, maternal education levels and the practice of washing hands with soap after feeding children are significantly associated with stunting. Social assistance programs such as the Family Hope Program/Program Keluarga Harapan (PKH) have reached 64% of beneficiaries but have not been effective in reducing stunting rates because there is still inaccuracy in targeting recipients. Conclusion: Accelerating stunting reduction in NTT requires a multi-sectoral approach involving improving sanitation infrastructure, increasing access to nutrition, health education, and optimizing social assistance programs. Monitoring and evaluation of policy implementation need to be improved to ensure the effectiveness of the interventions carried out. Novelty/Originality of this article: This study highlights the relationship between environmental factors, cultural practices, and policy effectiveness in accelerating stunting reduction in NTT. The SEM approach used offers a holistic perspective in understanding the complexity of the problem and designing more effective intervention strategies.